Electromagnetic Wave Propagation Considering Planar Array Antenna in Atmospheric Environments - Kim, Changseong; Lee, Soyeong; Yang, Junmo; Park, Yong Bae (International Conference on ICT Convergence, 2021)
We proposed a novel method to calculate the electromagnetic wave propagation considering planar array antenna in inhomogeneous and dispersive atmospheric environments. The method uses high-frequency approximation such as the ray tracing technique, geometrical optics. The atmospheric environments are considered by stratifying the atmosphere and calculating the electromagnetic wave propagation. The refractive index is calculated from meteorological data using millimeter-propagation-model93 and Appleton-Hartree equation to predict the electromagnetic wave propagation. Also, Interpolations are used to overcome limited observatories of meteorological data. In consideration of sun-synchronous orbit satellite passing through South Korea, atmospheric attenuation, received power, and boresight error are calculated and discussed.
Keywords: Atmospheric attenuation; Atmospheric environment; Boresight error; High frequency approximation; LEO satellite; Meteorological data; Millimeter propagation; Novel methods; Planar-array antennas; Ray-tracing technique; atmospheric attenuation; boresight error; LEO satellite; planar array antenna